Novel Mutations in the MKKS, BBS7, and ALMS1 Genes in Iranian Children with Clinically Suspected Bardet–Biedl Syndrome - Roghayeh Dehghan; Mahdiyeh Behnam; Mansoor Salehi; Roya Kelishadi (Case Reports in Ophthalmological Medicine)
Bardet–Biedl syndrome is a rare autosomal recessive form of syndromic obesity which is characterized by retinal degeneration, obesity, polydactyly, cognitive impairment, and renal and urogenital anomalies. In this study, we used whole-exome sequencing (WES) to investigate the underlying mutations in four Iranian children from consanguineous families with a clinical diagnosis of Bardet–Biedl syndrome (BBS). In three out of four children, we identified one previously reported frameshifting variant in the BBS12 gene (c.265-266delTT, p.L89fs) and two novel nonsense variants in MKKS (c.1196T>G, p.L399X) and BBS7 genes (c.1636C>T, p.Q546X). In the other child, no mutations were detected in known genes for BBS. However, we identified a novel variant in the ALMS1 gene (c.10996delC, p.Q3666fs) indicative of Alström syndrome. All variants were interpreted as pathogenic according to American College of Medical Genetics and Genomics (ACMG) guidelines and confirmed through Sanger sequencing. In conclusion, our results not only expand the spectrum of mutations in BBS and ALMS1 genes but also accentuate the importance of genetic testing for differentiating BBS from Alström syndrome.